PREVALENCE OF HOOKWORM INFECTION IN A SLUM AREA, VANGAYAGUDEM, WEST GODAVARI DISTRICT, (ANDHRA PRADESH) - R. INDIRA; V. VIVEKA VARDHANI (The Bioscan, 2010)
The prevalence of hookworm infection was ascertained in the rural areas of Eluru, West Godavari District, A.P. that are represented by only scheduled caste population at different periods of the year i.e. summer season, rainy season and winter season. Majority of the inhabitants are illiterate and coolies living in poor hygienic conditions. All the positive disease cases were found lodging Ancylostoma duodenale. The prevalence of hookworm infection was 17.3%, 29.3%, 16.3% in children and 37.2%, 48.2%, 17.4% in adults in summer, winter and rainy seasons respectively. Ancylostoma duodenale is the only infection in 264 samples, 92 children and 172 adults showed 41.6% of ancylostomiasis in rainy season. Different age groups like10-19, 20-29, 40-49, 50-59 and >60 years showed highest prevalence of ancylostomiasis. The infected individuals were treated with Albendazole just after rainy season. Antihelminthic treatment together with health education reduced the infection and promoted environmental health in the study area.